Climate and Disaster Risk Screening : Making Energy Projects More Resilient - Gessesse, Eskedar Bahru (World Bank, Washington, DC, 2021)
The power sector remains especially vulnerable to natural disasters and extreme weather events exacerbated by climate change. Planning ahead and investing in resilience to mitigate climate and disaster risks in the power sector can help minimize infrastructure damage and yield savings during recovery from a natural disaster. Conducting an in-depth climate and disaster risk screening (CDRS) during the planning and preparation stages of energy infrastructure projects is a crucial first step to building resilience. Data sharing, knowledge exchange, and awareness building on CDRS can substantially improve the screening process, while also helping to bring resilience to the forefront of energy investment discussions.